COM151: Fundamentals of multimedia system / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (2025)
This course is to introduce the fundamental concepts and principles of Multimedia system. Student will expose themselves theoretically and practically into various components of Multimedia such as text, graphics (and images), audio and video. Throughout the course, student will explore and experience each stage in Multimedia project development, and basic skill in the creation of the four Multimedia components. Upon completion of this course, student will be able to develop their own Multimedia project and able to understand the various types of Multimedia projects and delivery systems available in the current practices.